Design and analysis of a broadband vibratory energy harvester using bi-stable piezoelectric composite laminate. (1st August 2018) - Pan, Diankun; Dai, Fuhong
Highlights: A piezoelectric energy harvester based on bistable composite laminate is presented. A new stacking sequence design enhances this bistable energy harvester. A numerical model and a finite element model were established and validated. The harvester can generate high power under periodic cross-well vibration. Abstract: In this paper, a bi-stable piezoelectric energy harvester based on the bi-stable hybrid composite laminate with a new stacking sequence design is proposed. The new stacking sequence enables this bi-stable energy harvester to have some unique features, such as uniform strains of piezoelectric elements and symmetric stable configurations. Meanwhile, the new stacking sequence design enhances the room to adjust its natural frequency such that this proposed harvester allows for adjusting to lower frequency range and increasing the inertia by a tip mass to lower the demand of excitation level in comparison to previous settings. A finite element analysis is developed to investigate the static and dynamic characteristics of this new bi-stable energy harvester. A simple numerical model with a modified version of the Duffing equation is developed based on the unique nonlinear restoring force obtained from finite element analysis to describe the fundamental response characteristics of this nonlinear bi-stable energy harvester. Numerical simulations and experiments are carried out at different harmonic excitation levels ranging from 10 to 40 Hz. The results verify that the proposed model can reasonably capture the dynamic characteristics of this broadband bi-stable energy harvester. The output powers were measured under different vibration patterns. Maximum power of 31.1 mW was generated under large-amplitude and high-energy orbits cross-well vibration pattern at an excitation frequency of 22 Hz and acceleration of 3 g ( g  = 9.8 m/s 2 ).